Drawn from life: Cocreating narrative and graphic vignettes of lived experience with people affected by dementia. (10th August 2021) - Capstick, Andrea; Dennison, Alison; Oyebode, Jan; Healy, Lesley; Surr, Claire; Parveen, Sahdia; Sass, Cara; Drury, Michelle
Abstract: Background: The growing literature on Patient and Public Involvement and Engagement (PPIE) and dementia identifies specific problems related to the influence that involvement has on research outcomes, over‐reliance on family members as proxies and lack of representation of seldom‐heard groups. Adaptations to the PPIE process are therefore needed to make possible the involvement of a broader spectrum of people living with dementia. Objective: This study aimed to adapt the PPIE process to make participation in cocreation by people living with dementia accessible and meaningful across a spectrum of cognitive abilities. Design: Narrative elicitation, informal conversation and observation were used to cocreate three vignettes based on PPIE group members' personal experiences of dementia services. Each vignette was produced in both narrative and graphic formats. Participants: Nine people living with dementia and five family members participated in this study. Results: Using enhanced methods and outreach, it was possible to adapt the PPIE process so that not only family members and people with milder cognitive difficulties could participate, but also those with more pronounced cognitive problems whose voices are less often heard. Conclusions: Making creative adaptations is vital in PPIE involving people living with dementia if we wish to develop inclusive forms of PPIE practice. This may, however, raise new ethical issues, which are briefly discussed. Patient or Public Contribution: People with dementia and their families were involved in the design and conduct of the study, in the interpretation of data and in the preparation of the manuscript.